Biomechanical-Based Protocol for in vitro Study of Cartilage Response to Cyclic Loading: A Proof-of-Concept in Knee Osteoarthritis - Caravaggi, Paolo; Assirelli, Elisa; Ensini, Andrea; Ortolani, Maurizio; Mariani, Erminia; Leardini, Alberto; Neri, Simona; Belvedere, Claudio (Frontiers in Bioengineering and Biotechnology, 2021)
Osteoarthritis (OA) is an evolving disease and a major cause of pain and impaired mobility. A deeper understanding of cartilage metabolism in response to loading is critical to achieve greater insight into OA mechanisms. While physiological joint loading helps maintain cartilage integrity, reduced or excessive loading have catabolic effects. The main scope of this study is to present an original methodology potentially capable to elucidate the effect of cyclic joint loading on cartilage metabolism, to identify mechanisms involved in preventing or slowing down OA progression, and to provide preliminary data on its application. In the proposed protocol, the combination of biomechanical data and medical imaging are integrated with molecular information about chondrocyte mechanotransduction and tissue homeostasis. The protocol appears to be flexible and suitable to analyze human OA knee cartilage explants, with different degrees of degeneration, undergoing ex vivo realistic cyclic joint loading estimated via gait analysis in patients simulating mild activities of daily living. The modulation of molecules involved in cartilage homeostasis, mechanotransduction, inflammation, pain and wound healing can be analyzed in chondrocytes and culture supernatants. A thorough analysis performed with the proposed methodology, combining in vivo functional biomechanical evaluations with ex vivo molecular assessments is expected to provide new insights on the beneficial effects of physiological loading and contribute to the design and optimization of non-pharmacological treatments limiting OA progression.